A comparative study between the Damara and the German Merino with respect to the influence of certain environmental stress factors - Meissner, Heinz Herbert (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc. (Agric.)) -- University of Stellenbosch, 1971.